2009
DOI: 10.1039/b912589m
|View full text |Cite
|
Sign up to set email alerts
|

JEM Spotlight: Environmental monitoring of airborne nanoparticles

Abstract: The aim of this work was to review the existing instrumental methods to monitor airborne nanoparticles in different types of indoor and outdoor environments in order to detect their presence and to characterise their properties. Firstly the terminology and definitions used in this field are discussed, which is followed by a review of the methods to measure particle physical characteristics including number, concentration, size distribution and surface area. An extensive discussion is provided on the direct met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 177 publications
1
43
0
Order By: Relevance
“…The deviations among both instruments were considered not statistically significant (p-value > 0.05) ( Table 2 and Figure 2). This difference in NanoScan performance for the DEHS aerosols may be caused by the fact that the Cunningham slip correction factor gets an increasingly weak function of particle diameter with increasing particle size and eventually even passes a minimum (Levin et al 2015), and hence the electrical mobility of unipolar diffusion charged particles (as acquired in the NanoScan) also becomes less sensitive in measuring the particle diameter (Morawska et al 2009b) by acquiring a charge level which is nearly proportional to the particle diameter (Jung and Kittelson 2005;Asbach et al 2011). It should be noted that a constant and unexpected peak was detected around 22-27 nm with NanoScan in each experimental run with DEHS particles, and it is also suggested by the SMPS-L data.…”
Section: Compact and Spherical Particlesmentioning
confidence: 99%
“…The deviations among both instruments were considered not statistically significant (p-value > 0.05) ( Table 2 and Figure 2). This difference in NanoScan performance for the DEHS aerosols may be caused by the fact that the Cunningham slip correction factor gets an increasingly weak function of particle diameter with increasing particle size and eventually even passes a minimum (Levin et al 2015), and hence the electrical mobility of unipolar diffusion charged particles (as acquired in the NanoScan) also becomes less sensitive in measuring the particle diameter (Morawska et al 2009b) by acquiring a charge level which is nearly proportional to the particle diameter (Jung and Kittelson 2005;Asbach et al 2011). It should be noted that a constant and unexpected peak was detected around 22-27 nm with NanoScan in each experimental run with DEHS particles, and it is also suggested by the SMPS-L data.…”
Section: Compact and Spherical Particlesmentioning
confidence: 99%
“…The upper size detection limit of the NAIS effectively restricts it to the nanoparticle size range, which has somewhat arbitrarily been defined as smaller than 50 nm (Morawska et al, 2009). Particles in vehicle emissions, particularly soot, have a mode between 50 and 100 nm.…”
Section: Instrumentationmentioning
confidence: 99%
“…There is a plausible explanation for these observations. Most of the particles in an NPF event are secondary volatile particles that are in the nanoparticle size range (Morawska et al, 2009) while the particles produced by fireworks and bush burning consist of mostly primary soot that are much larger in size. Airborne measurements of PNC near biomass burning events in the Northern Territory, Australia (Ristovski et al, 2010), showed that the median diameter of smoke particles were about 90 nm when the flight paths were close to the fires.…”
Section: General Trends Of Cic Versus Pncmentioning
confidence: 99%
“…In this way, the NAIS can measure positive and negative cluster ions and charged particle concentrations simultaneously as well as neutral clusters and particles in the mobility range 3.16 to 0.001 cm 2 /V / s, which corresponds to a mobility size range of 0.8 to 42 nm. The upper size detection limit of the NAIS effectively restricts it to the nanoparticle size range, which has somewhat arbitrarily been defined as smaller than 50 nm (Morawska et al, 2009). Therefore, all PNCs in this paper refer to nanoparticles only.…”
Section: Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation